ENTRE A CEGUEIRA E A ALTERIDADE: A METÁFORA COMO CHAVE DE LEITURA TEOLÓGICA NO ENSAIO SOBRE A CEGUEIRA - OLIVEIRA, DAIANA DUTRA DE (2021)
Theology and literature, whose relationships for centuries alternated between approximations and distances, will be seen in this research as part of the field of theopoetics. This one was established with the purpose that the two areas of knowledge could have their relations narrowed by the theological perspective. The investigation, whose object is the novel Essay on blindness, will feature a bibliographical review containing works that deal with the relationship between literature and theology and the presence of metaphor in the work. Written in the form of an essay, the object still has a timid space in this field of studies. Although his investigation takes place in different areas of knowledge due to the social criticism woven into the narrative. In this way, his research in the area becomes relevant, given the fact that it is a work, whose theological possibility is not perceived at first glance. From this perspective, the objective is to identify and reflect on the connection between the two knowledges in the object. More specifically, to point out descriptions of theopoetics to indicate the possibilities of theological approaches to the work; indicate the importance of the work in the field of theopoetics with a view to identifying it as a metaphor for life; and finally, to report its proximity to theology through metaphor. For the metaphorical approach, Ricoeur's conceptualization will be used with his proposal of a living metaphor. Faced with this challenge, the work will be investigated as a possibility of social reading in an interpretation of life, through its metaphorical character. The network of metaphors that guides it may suggest that white blindness metaphorizes the human condition in today's society. Thus, suspicions fall on which attitude can bring about the necessary changes for social re-establishment. If it is possible to find traces of this action in the work, the alterity that is metaphorized in the essay by the doctor's wife will be considered the path to be followed. Karl-Josef Kuschel's Structural Analogy Method will guide the course of this research.